Traumatic abdominal wall hernia - Tanvir Kabir Chowdhury; Md Afruzul Alam; M.A. Mushfiqur Rahman; Rajib Khastagir; Rumana Khan (Elsevier, 2020)
Traumatic abdominal wall hernia (TAWH) is uncommon in children and most cases are related to handle bar injury. We report a case of TAWH and pelvic fracture following road traffic accident at an unusual site. Part of the transverse colon, along with its mesocolon, was herniated into a defect in the wall of left lower chest and of left upper quadrant of abdomen. Laparotomy was done and the hernial defect was repaired.